Methods Of Reactive Power Compensation In The Load Of Photoelectric Installations In Central Asia - Rakhimov A.A. (Genius Journals, 2022)
In this article, opinions and feedback on DC converters and reactive power compensation at their load, photoelectric sistems and its results are discussed, which determine the advantages and energy and economic efficiency of energy efficient unchanging current exchangers for solar batteries
Keywords: photoelectric solar battery; energy efficient; constant current converter; reactive power